2017
DOI: 10.3389/fimmu.2017.01295
|View full text |Cite
|
Sign up to set email alerts
|

Association between Systemic Lupus Erythematosus and Periodontitis: A Systematic Review and Meta-analysis

Abstract: BackgroundSystemic lupus erythematosus (SLE) is a chronic systemic inflammatory autoimmune disease, the etiology of which remains only partially characterized. Strong evidence implicates chronic infections in the development and chronicity of autoimmune conditions. Recently, an association has been demonstrated between periodontitis and rheumatoid arthritis. Such observations have led to the investigation of the possible role of periodontitis and oral dysbiosis in other systemic inflammatory conditions, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 34 publications
7
54
0
Order By: Relevance
“…Oral manifestations of SLE are frequently encountered [ 13 ] and may include oral ulceration, honeycomb plaque, raised keratotic plaque, nonspecific erythema, purpura, petechiae, and cheilitis [ 14 ]. Research shows that 25% of SLE patients have oral mucous membrane and lip involvement with possible petechiae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral manifestations of SLE are frequently encountered [ 13 ] and may include oral ulceration, honeycomb plaque, raised keratotic plaque, nonspecific erythema, purpura, petechiae, and cheilitis [ 14 ]. Research shows that 25% of SLE patients have oral mucous membrane and lip involvement with possible petechiae.…”
Section: Introductionmentioning
confidence: 99%
“…A high prevalence of oral complaints such as dysphagia, dysgeusia, and glossodynia was also present [ 15 ]. A recent systematic review reported a significant association between periodontitis and SLE [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…As lupus patients has elevated levels of pro-inflammatory cytokines [37], is expected that they have higher risk to develop periodontal disease. The significant increase in periodontitis in patients with lupus might be related to their susceptibility to periodontal disease by its inherent host response due to the disease itself [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis is one of chronic infectious diseases destructing the alveolar bone and the supportive tissue of the teeth; it is also associated with a variety of systemic diseases such as diabetes, cardiovascular disease, and premature low birth weight [ 17 19 ]. The periodontal ligament comes from dental follicle, derived from neural crest cells, and PDLSCs play critical roles in periodontal ligament.…”
Section: Discussionmentioning
confidence: 99%